1999
DOI: 10.1111/j.1939-1676.1999.tb02172.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Feline Chlamydia psittaci and Feline Herpesvirus 1 in Cats with Upper Respiratory Tract Disease

Abstract: The epidemiology of feline chlamydiosis and feline herpesvirus 1 (FHV1) infection in cats was determined using a duplex poly-merase chain reaction assay. In cats with upper respiratory tract disease (URTD), prevalences of 66 (14.3%) of 462 cats and 98 (21.2%) of 462 cats were found for Chlamydia psittaci and FHV1, respectively. In cats without URTD, prevalences were 1/87 (1.1%) for both pathogens. Younger cats, cats sampled in summer, and cats with conjunctivitis were more likely to be positive for C psittaci … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
4
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 21 publications
(14 reference statements)
4
44
4
1
Order By: Relevance
“…Because C. felis is a conjunctival pathogen and corneal samples are rarely positive, 7,12 the low detection rate in our study may be explained by the lack of conjunctival samples in 16 of 23 (70%) cats with clinical signs. In addition, earlier studies have shown a higher prevalence for C. felis in younger cats, whereas the mean age of the cats with clinically signs in our study was relatively high 13,14 …”
Section: Discussioncontrasting
confidence: 49%
See 3 more Smart Citations
“…Because C. felis is a conjunctival pathogen and corneal samples are rarely positive, 7,12 the low detection rate in our study may be explained by the lack of conjunctival samples in 16 of 23 (70%) cats with clinical signs. In addition, earlier studies have shown a higher prevalence for C. felis in younger cats, whereas the mean age of the cats with clinically signs in our study was relatively high 13,14 …”
Section: Discussioncontrasting
confidence: 49%
“…Sykes et al . showed that detection of FHV‐1 DNA was less common if disease had been present for longer than 1 week 13 . A third possible explanation could be a lower prevalence of FHV‐1 in the area of Sweden where samples in the present study were collected.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…[77]. The association of OAL with C. psittaci has been reported mostly in subjects coming from rural areas, following a prolonged contact with household animals [8].…”
Section: Chlamydiae Spp and Their Role In Chronic Diseases And In Camentioning
confidence: 99%